Pengaruh Perubahan Iklim Terhadap Keanekaragaman Hayati Di Kawasan Tropis - Halawa, Lola Sri Wahyuni; Zakiyah, Umi (CV. SINAR HOWUHOWU, 2025)
Climate change significantly impacts biodiversity in tropical regions, known as areas with the highest biodiversity levels globally. Rising global temperatures, shifting rainfall patterns, and extreme weather events disrupt ecosystem stability, causing habitat degradation, population declines, and even extinction of endemic species. This study aims to examine the effects of climate change on tropical ecosystems and explore applicable mitigation and adaptation strategies. The analysis reveals that species in tropical regions are highly vulnerable to environmental changes due to their dependence on stable climatic conditions. Ecosystem-based conservation, habitat restoration, and reducing greenhouse gas emissions are essential steps to ensure the sustainability of tropical biodiversity. Collaborative efforts among governments, scientists, and communities are necessary to minimize the impacts of climate change on tropical biodiversity.